2011
DOI: 10.1158/1940-6207.capr-11-0176
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Resistant Starch of Red Meat–Induced Promutagenic Adducts in Mouse Colon

Abstract: Population studies have shown that high red meat intake may increase colorectal cancer risk. Our aim was to examine the effect of different amounts and sources of dietary protein on induction of the promutagenic adduct O 6 -methyl-2-deoxyguanosine (O 6 MeG) in colonocytes, to relate these to markers of large bowel protein fermentation and ascertain whether increasing colonic carbohydrate fermentation modified these effects. Mice (n ¼ 72) were fed 15% or 30% protein as casein or red meat or 30% protein with 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 45 publications
2
78
1
Order By: Relevance
“…Rodent studies have shown that resistant starch can raise colonic butyrate levels, alter gut microbiota abundance, reduce adenocarcinoma formation in response to a carcinogen, and attenuate red meat-induced DNA damage (5,11,22,38). In this human study, supplementation with butyrylated resistant starch significantly raised fecal butyrate levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent studies have shown that resistant starch can raise colonic butyrate levels, alter gut microbiota abundance, reduce adenocarcinoma formation in response to a carcinogen, and attenuate red meat-induced DNA damage (5,11,22,38). In this human study, supplementation with butyrylated resistant starch significantly raised fecal butyrate levels.…”
Section: Discussionmentioning
confidence: 99%
“…20 and 21). In rodents, resistant starch supplementation to an HRM diet increased colonic butyrate, altered gut microbiota, decreased inflammation, and attenuated red meat-induced DNA damage (3,5,22). HAMSB was more effective than standard amylose maize starch in lowering genetic damage (23).…”
Section: Introductionmentioning
confidence: 97%
“…Increased dietary heme from haemoglobin in 299 red meat can form reactive oxygen species, [37] Sesink 300 et al [38] showed that dietary heme increases luminal 301 cytotoxicity which causes damage to the colonic 302 epithelium. Previous animal studies by us have also shown 303 that red meat consumption results in a thinning of the 304 colonic mucus layer and increases damage to the colono-305 cytes in the form of DNA strand breaks [39] or pro-306 mutagenic adducts [40]. 307 Mice consuming RS along with the red meat diet had 308 reduced clinical signs of colitis when compared to mice fed 309 only the red meat diet.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 97%
“…68,69 The combination of heme-containing proteins as they occur in red meat was evaluated only in studies that provided meat. 21,22,59 Myoglobin is a ubiquitous and significant form of heme iron in red meat and the use of surrogates, such as hemin or isolated hemoglobin, are not equivalent to meat.…”
Section: Impact Of Study Designs and Experimental Approachesmentioning
confidence: 99%